2020
DOI: 10.1016/j.nut.2019.110583
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of the combination Bifidobacterium longum plus lactoferrin against NSAID-induced enteropathy

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 38 publications
1
24
1
1
Order By: Relevance
“…A recent publication examined the protective effects of a combination of the probiotic Bifidobacterium longum BB536 (2.5 × 106 CFU/rat twice daily) with the prebiotic lactoferrin (100 mg/kg twice daily) in a rat model of diclofenac-induced enteropathy [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…A recent publication examined the protective effects of a combination of the probiotic Bifidobacterium longum BB536 (2.5 × 106 CFU/rat twice daily) with the prebiotic lactoferrin (100 mg/kg twice daily) in a rat model of diclofenac-induced enteropathy [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the administration of Bifidobacterium adolescentis or Faecalibacterium prausnitzii prior naproxen treatment results in a significant reduction of the intestinal damage in rats, probably through an effect on the biosynthesis of cytoprotective short-chain fatty acids (Syer et al, 2015). Recently, it has been reported that the combination of lactoferrin with Bifidobacterium longum protects against diclofenac induced-enteropathy in rats partially by modulating the TLR-2/-4/NF-kB pathways (Fornai et al, 2020). So far, few studies have been performed in humans to investigate whether modulation of the gut microbiota with probiotics is an effective therapeutic approach against NSAID-induced enteropathy, and the results of these studies are discordant (Montalto et al, 2013).…”
Section: Therapeutic Interventions Targeting the Gut Microbiotamentioning
confidence: 99%
“…Furthermore, the administration of Bifidobacterium adolescentis or Faecalibacterium prausnitzii prior naproxen treatment results in a significant reduction of the intestinal damage in rats, probably through an effect on the biosynthesis of cytoprotective short-chain fatty acids ( Syer et al., 2015 ). Recently, it has been reported that the combination of lactoferrin with Bifidobacterium longum protects against diclofenac induced-enteropathy in rats partially by modulating the TLR-2/-4/NF- κ B pathways ( Fornai et al., 2020 ).…”
Section: Therapeutic Interventions Targeting the Gut Microbiotamentioning
confidence: 99%
“…Lactobacillus fermentum cell-free supernatant (LCFS) caused cancer cell death in 3D HCT-116 conditions through the induction of apoptosis in the colon cancer cell line and the antiproliferative activity by the inhibition of NF-κB signaling [129]. The use of lactoferrin and Bifidobacterium longum BB536 managed the enteropathy caused by diclofenac in rat samples by modulating the proinflammatory pathway of TLR-2/-4/NF-kB [130]. Othman et al [131], studied the effect of inactivated Bifidobacterium longum intake on obese diabetes affected mice.…”
Section: Health Promoting Effect Of Prebiotics Probiotics and Synbimentioning
confidence: 99%